1996
DOI: 10.1017/s0043174500093486
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis for Differential Sensitivity to Sulfentrazone by Sicklepod (Senna obtusifolia) and Coffee Senna (Cassia occidentalis)

Abstract: Consistent with field observations, sicklepod exhibited considerable tolerance to sulfentrazone, and coffee senna showed relatively high sensitivity to this herbicide in greenhouse tests. Germination was not inhibited in either species at up to 12.9 μM of the herbicide. However, the chlorophyll content of herbicide-treated coffee senna cotyledonary leaves was greatly reduced, and seedlings died within 10 d after treatment, while sicklepod seedlings were not visibly affected. Shoot height of coffee senna was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 23 publications
4
68
0
1
Order By: Relevance
“…The presence of this compound is the evidence that some microbial degradation is occurring in the soil and that either fungi or bacteria can metabolize the herbicide. The formation of this derivative is known to be achieved through a stepwise oxidation of the triazolinone ring methyl group of the parent molecule, and it is known to be less toxic than sulfentrazone (Dayan et al, 1996(Dayan et al, , 1998 with respect to its biological activity (Theodorides et al, 1992). The metabolisms of sulfentrazone in animals and plants are similar; the major plant metabolite being 3-hydroxymethyl sulfentrazone (HMS).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this compound is the evidence that some microbial degradation is occurring in the soil and that either fungi or bacteria can metabolize the herbicide. The formation of this derivative is known to be achieved through a stepwise oxidation of the triazolinone ring methyl group of the parent molecule, and it is known to be less toxic than sulfentrazone (Dayan et al, 1996(Dayan et al, , 1998 with respect to its biological activity (Theodorides et al, 1992). The metabolisms of sulfentrazone in animals and plants are similar; the major plant metabolite being 3-hydroxymethyl sulfentrazone (HMS).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Thomas et al (2005) in peanut and prickly sida (sulfentrazone-tolerant and -susceptible species, respectively). Dayan et al (1996) also reported that sulfentrazone-tolerant and -susceptible weed species did not differ in root uptake of sulfentrazone. Therefore, the uptake and translocation of sulfentrazone observed in tobacco was consistent with other research and is apparently not the mechanism of tolerance in tobacco.…”
Section: Resultsmentioning
confidence: 89%
“…In treatments with M, M was added at 0.5% (v/v). Treatments were applied as 10 Table 1), on the biomass of conventional canola. Data are expressed as a percent of untreated controls.…”
Section: Resultsmentioning
confidence: 99%